2017
DOI: 10.1292/jvms.16-0560
|View full text |Cite
|
Sign up to set email alerts
|

Phloridzin inhibits high K<sup>+</sup>-induced contraction via the inhibition of sodium: glucose cotransporter 1 in rat ileum

Abstract: Recent studies have shown that phloridzin, an inhibitor of sodium–glucose cotransporter (SGLT), strongly decreases high K+-induced contraction in phasic muscle, such as tenia coli, but slightly affects tonic muscle, such as trachea . In this study, we examined the inhibitory mechanism of phloridzin on high K+-induced muscle contraction in rat ileum, a phasic muscle. Phloridzin inhibited the high K+-induced contraction in the ileum and the aorta, and the relaxing effect of phloridzin at 1 mM in the ileum was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Wang et al [ 103 ] found that extracts from the fruits of Malus baccata contained phloridzin, and the extracts had radioprotective and immunomodulatory activities. Kanda et al [ 104 ] found that phloridzin strongly decreased high K + -induced contraction in phasic muscle (tenia coli), but slightly affected tonic muscle (trachea) because of the inhibition of energy metabolism via SGLT1. Li et al [ 105 ] found that phloridzin increased NO output, suppressed SGLT1 and SGLT2 expression, and promoted the consumption of glucose, which ameliorated endothelial dysfunction by the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/endothelial nitric oxide synthase (eNOS) signaling pathway in palmitic acid-induced human umbilical vein endothelial cells.…”
Section: Therapeutic Properties Of Phloridzinmentioning
confidence: 99%
“…Wang et al [ 103 ] found that extracts from the fruits of Malus baccata contained phloridzin, and the extracts had radioprotective and immunomodulatory activities. Kanda et al [ 104 ] found that phloridzin strongly decreased high K + -induced contraction in phasic muscle (tenia coli), but slightly affected tonic muscle (trachea) because of the inhibition of energy metabolism via SGLT1. Li et al [ 105 ] found that phloridzin increased NO output, suppressed SGLT1 and SGLT2 expression, and promoted the consumption of glucose, which ameliorated endothelial dysfunction by the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/endothelial nitric oxide synthase (eNOS) signaling pathway in palmitic acid-induced human umbilical vein endothelial cells.…”
Section: Therapeutic Properties Of Phloridzinmentioning
confidence: 99%